2018
DOI: 10.3390/hydrology5010014
|View full text |Cite
|
Sign up to set email alerts
|

The Climate Change Vulnerability and Risk Management Matrix for the Coastal Zone of The Gambia

Abstract: Global Climate Change is one of the dire challenges facing the international community today. Coastal zones are vulnerable to its impacts. An effective approach with long-term prospects in addressing climate change impacts is it's mainstreaming into development agenda of sectoral policies. A comprehensive risk and vulnerability assessment is a pre-requisite to ensure that the right adaptive response is taken for effective integration into developmental plans. The objective of this study is to evaluate and prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 55 publications
0
27
0
1
Order By: Relevance
“…This variability has increased since the 1950s, and particularly during the latest decade [1]. This is principally due to the increased concentration of anthropogenic greenhouse gases in the atmosphere as argued by some authors [2][3][4][5][6][7][8]. Global surface temperature has increased by 0.71 • C over the last century with significant warming observed in many regions [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This variability has increased since the 1950s, and particularly during the latest decade [1]. This is principally due to the increased concentration of anthropogenic greenhouse gases in the atmosphere as argued by some authors [2][3][4][5][6][7][8]. Global surface temperature has increased by 0.71 • C over the last century with significant warming observed in many regions [3].…”
Section: Introductionmentioning
confidence: 99%
“…This is principally due to the increased concentration of anthropogenic greenhouse gases in the atmosphere as argued by some authors [2][3][4][5][6][7][8]. Global surface temperature has increased by 0.71 • C over the last century with significant warming observed in many regions [3]. This increase in global mean surface temperature in recent times reveals more warming of land than the oceans with diverse consequences on the livelihood of people [3,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, promotion of alternative sources of energy will contribute towards development aspirations of the study area in many important ways: (1). saving trees that would otherwise be cut down for charcoal or firewood production to increase carbon dioxide sequestration; (2).…”
Section: Recommendationsmentioning
confidence: 99%
“…Studies have shown that climate change has become a major threat to agriculture, particularly in developing countries [1][2][3]. Farmers in African countries have been identified as most vulnerable to climate change due to their low adaptive capacities [4][5][6].…”
Section: Introductionmentioning
confidence: 99%